Corporal Artistic Training Influences Attention: A Pilot Study. Issue 3 (June 2014) - Ribeiro, Mônica Medeiros; Lima, Isabela; Malloy-Diniz, Leandro; Lage, Guilherme; Pimentel, Lucia Gouvêa; Teixeira, Antônio Lúcio
This study assessed the effect of the Body Rhythmics (BRIM) on actors' attentional processes. BRIM is a combination of exercises using numbers and rules that enact musical parameters in the moving body through displacements. Male actors ( N = 22) participated in the study: 7 in the BRIM (Study) group and 15 in the Control group (groups were equivalent on mean Raven's IQ). The Continuous Performance Test (CPT–II) was administered before and after an intensive period of BRIM training. There was no significant difference on the CPT–II before training. Group results for before vs after training showed a significant difference for reaction time for the Study group. There was also a trend to increased errors of commission in the Study group after BRIM training.